Arundo smaragdina (Poaceae): a novel species revealed by integrative taxonomy and its implications for the phylogeny of the genus - Liu, Fupeng; Li, Boyu; He, Qingmeng; Zhao, Aixuan; Xi, Ben; Shen, Xiaotong (Frontiers in Plant Science, 2025)
IntroductionArundo species have long served as vital raw materials for human livelihoods, yet their phylogenetic relationships remained poorly resolved until recent decades.MethodsThis study identifies a novel species, Arundo smaragdina, through integrative analyses of morphology, multiple nucleotide polymorphism (MNP) markers, and chloroplast genome data, and elucidates its phylogenetic placement within the genus.ResultsA. smaragdina is characterized by 72 chromosomes (2n=72), solid and limited rhizomes, erect and branched culms, glabrous nodes, and inflorescences emerging in early September. Mature inflorescences contain 2–5 florets per spikelet, with lemma hairs perpendicularly inserted at the basal region, and the pollen germination rate averages 12.7%. Within the genus, A. formosana is confirmed as the basal species. A. donax (a species potentially of Asian origin) differs from A. smaragdina in having spreading rhizomes and lemma hairs obliquely distributed on the lower quarter, although both species share morphological convergence and similar yields. While A. smaragdina is distinct from the Mediterranean A. plinii complex (including A. plinii, A. donaciformis, and A. micrantha), which possesses hollow rhizomes and 1(2) florets per spikelet, it shares similar pollen germination rates and chromosome numbers with some clones of A. plinii, and exhibits parallels with A. micrantha in yield, chromosome count, and branched culm architecture. At the molecular level, MNP markers confirm the genomic distinctiveness of A. smaragdina from A. donax, while chloroplast phylogeny reveals its intermediate phylogenetic position between A. donax and the A. plinii complex. Molecular dating estimates divergence times of approximately 2.29 million years ago (Mya) from A. plinii and ~2.9 Mya from A. donax.DiscussionThe congruent morphological and molecular evidence suggests that A. smaragdina may have played a pivotal role in the evolution of Arundo species.